PdAgRu nanoparticles on polybenzimidazole wrapped CNTs for electrocatalytic formate oxidation. (10th September 2020) - Gebremariam, Tesfaye Tadesse; Chen, Fuyi; Kou, Bo; Guo, Longfei; Pan, Bowei; Wang, Qiao; Li, Zhen; Bian, Weiqi
Abstract: Direct formate fuel cells (DFFCs) have received great interest as potential candidates of power sources, and their viability primarily relies on exploration of efficient formate oxidation reaction (FOR) catalysts. Herein, we have prepared PdAgRu nanoparticles supported on polybenzimidazole wrapped carbon nanotubes (pCNTs), Pd6 Ag3 Ru1 /pCNTs catalyst which displays remarkable mass activity of 4.7 A mgPd −1 and maintains current density of 0.71 A mg −1 after 5400 s of chronoamperometry test, which is 2.1 and 26.7 times better than that of commercial Pd/C catalyst, respectively. The performance improvement is attributed to delicately designed components, polybenzimidazole layer serves as hydroxide transporter, carbon nanotubes function as electron conductive path, Ag weakens binding strength of adsorbed hydrogen (Hads ) on Pd, and Ru promotes the formation of hydroxyl species. Impressively, when the upper limit potential of cyclic voltammetry is enlarged into Ag redox region, the FOR activity remarkably increases, the mass activities are 4.30, 4.7 and 5.12 A mgPd −1 at 1.1, 1.3 and 1.5 V, respectively. The closer examination of x-ray photoelectron spectroscopy (XPS) spectra reveal the co-existence of mixed Pd(0)/Pd(II) and Ag(0)/Ag(I) state on the catalyst surface. The amount of Pd(0) and Ag(I) state increase with increasing upper limit potential, which is attributed to surface restructuration. Graphical abstract: Image 1 Highlights: PdAgRu nanoparticles on polybenzimidazole wrapped CNTs (Pd6 Ag3 Ru1 /pCNTs) is prepared. pCNTs uniformly immobilize the nanoparticles and serve as hydroxide and electron conductive path. Pd6 Ag3 Ru1 /pCNTs catalyst manifests improved catalytic performance toward FOR. When CV is recorded at higher upper limit potential Pd6 Ag3 Ru1 /pCNTs displays improved FOR activity. The Hads binding strength is significantly weakened via the electronic and oxophilic effect.